Axial crushing behaviour of honeycomb-filled square carbon fibre reinforced plastic (CFRP) tubes. (15th April 2016) - Hussein, Rafea Dakhil; Ruan, Dong; Lu, Guoxing; Sbarski, Igor
Abstract: Experimental investigations were conducted to study the axial crushing behaviour of aluminium honeycomb-filled square carbon fibre reinforced plastic (CFRP) tubes. Axial compressive loads were applied to both hollow and honeycomb-filled CFRP tubes at constant velocities of 0.05 mm/s, 0.5 mm/s, 5 mm/s and 50 mm/s, respectively. Experimental results show that the deformation mode of hollow CFRP tubes with 100 mm length was a catastrophic failure mode. However, experimental deformation modes of hollow and aluminium honeycomb-filled CFRP tubes with 50 mm length were found to be a combination of splaying progressive failure and transverse shearing failure. The mean crushing force (MCF) and energy absorbed (EA) by honeycomb-filled CFRP tubes were larger than those of corresponding hollow CFRP tubes and, in general, these parameters were found to decrease with an increase in a crushing velocity. However, the specific energy absorption (SEA) of aluminium honeycomb-filled CFRP tubes was found to be less than that of a hollow CFRP tube. The effects of using adhesive and different gaps between the honeycomb core and CFRP tube walls were also examined. The energy absorption and specific energy absorption of hollow CFRP tubes, aluminium honeycomb-filled CFRP tubes and metal tubes were also compared.